Canadian money and banking - O'Brien, John W.; Lermer, George (Toronto : New York [etc., 1969)
This edition is quite different from the first. This is true of the format, the style and the topics covered. The primary purpose of the book is to be a teaching instrument.
Bibliography: p. 344-359.
osc 29/3/18
Loans
Keywords: Banks and banking; Monetary policy